Cranial osteology and systematic implications in Crotophaginae (Aves, Cuculidae) - Posso, SR; Donatelli, Reginaldo José [UNESP] (Blackwell Verlag Gmbh, 2001)
Recognizing the scarcity of anatomical and phylogenetic studies on Crotophaginae, the authors set Out to add to the anatomical knowledge of the group based on a detailed description of cranial osteology. Another objective was to verify whether this source of data could be used to infer relationships by performing the first cladistic analysis of the four species of Crotophaginae. The shortest-length cladogram (consistency index = 1.0) indicated that cranial osteology is an important source of characters for cladistic analysis of cuckoos. The findings corroborated the monophyly of Crotophaginae, showing that Guira guira is (lie most divergent and plesiomorphic taxon and that Crotophaga ani and Crotophaga sulcirostris are more closely related to each other than to Crotophaga major.
Keywords: Crotophaginae; Cuculidae; cranial osteology; cladistic analysis